Synergistic effect of leptin and lipidized PrRP on metabolic pathways in ob/ob mice - Kořínková, Lucia; Holubová, Martina; Neprašová, Barbora; Hrubá, Lucie; Pražienková, Veronika; Bencze, Michal; Haluzík, Martin; Kuneš, Jaroslav; Maletínská, Lenka; Železná, Blanka (Journal of molecular endocrinology, 2020)
Lack of leptin production in ob/ob mice results in obesity and prediabetes that could be partly reversed by leptin supplementation. In the hypothalamus, leptin supports the production of prolactin-releasing peptide (PrRP), an anorexigenic neuropeptide synthesized and active in the brain. In our recent studies, the palmitoylated PrRP analog palm11-PrRP31 showed a central anorexigenic effect after peripheral administration. This study investigates whether PrRP could compensate for the deficient leptin in ob/ob mice. In two separate experiments, palm11-PrRP31 (5 mg/kg) and leptin (5 or 10 μg/kg) were administered subcutaneously twice daily for 2 or 8 weeks to 8- (younger) or 16-(older) week-old ob/ob mice, respectively, either separately or in combination. The body weight decreasing effect of palm11-PrRP31 in both younger and older ob/ob mice was significantly powered by a subthreshold leptin dose, the combined effect could be then considered synergistic. Leptin and palm11-PrRP31 also synergistically lowered liver weight and blood glucose in younger ob/ob mice. Reduced liver weight was linked to decreased mRNA expression of lipogenic enzymes. In the hypothalamus of older ob/ob mice, two main leptin anorexigenic signaling pathways, namely, Janus kinase, signal transducer and activator of transcription-3 activation and AMP-activated protein kinase de-activation, were induced by leptin, palm11-PrRP31, and their combination. Thus, palm11-PrRP31 could partially compensate for leptin deficiency in ob/ob mice. In conclusion, the results demonstrate a synergistic effect of leptin and our lipidized palm11-PrRP31 analog.
Keywords: leptin; myši obézní; Male; Leptin; Obesity; přijímání potravy; Mice, Obese; obezita; Metabolic Networks and Pathways; mužské pohlaví; Drug Synergism; Eating; metabolismus lipidů; Prolactin-Releasing Hormone; Body Weight; synergismus léků; tělesná teplota; Animals; játra; zvířata; Lipid Metabolism; metabolické sítě a dráhy; myši; Body Temperature; Glucose Tolerance Test; hormon uvolňující prolaktin; Liver; Mice; tělesná hmotnost; glukózový toleranční test